2024
DOI: 10.3390/jcm13061586
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris Infection, a Rapidly Emerging Threat in the Neonatal Intensive Care Units: A Systematic Review

Rozeta Sokou,
Alexia Eleftheria Palioura,
Paschalia Kopanou Taliaka
et al.

Abstract: (1) Background: In recent years, a global epidemiological shift in candidemia has been observed, marked by the emergence of resistant non-albicans Candida species. Candida auris, in particular, has become a significant global concern, causing infections in both pediatric and adult populations within healthcare settings. Despite its widespread impact, there is a limited understanding of the clinical course and transmission dynamics of neonatal systemic Candida auris infections, hindering effective prevention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…In a review by Sokou R et al from 2024, 24 studies in neonates that were positive for this yeast were identified. The authors underlined the need of understanding Candida auris , whose pathogenesis is very important for developing effective strategies to control and prevent neonatal infections caused by this pathogen [ 40 ].…”
Section: Candida Auris : Multidisciplinary Involvementmentioning
confidence: 99%
“…In a review by Sokou R et al from 2024, 24 studies in neonates that were positive for this yeast were identified. The authors underlined the need of understanding Candida auris , whose pathogenesis is very important for developing effective strategies to control and prevent neonatal infections caused by this pathogen [ 40 ].…”
Section: Candida Auris : Multidisciplinary Involvementmentioning
confidence: 99%
“…Candida infection ranks as the third most common cause of neonatal late-onset sepsis, with Candida albicans being the most frequently isolated species. However, there has been a recent increase in the incidence of non-albicans Candida sepsis ( 13 ), including Candida glabrata, a case of which is reported by Parramon-Teixido et al describing a urinary tract infection in a preterm neonate.…”
mentioning
confidence: 99%